Neurocommunication in videogames: reaching an over-stimulated public - Barrientos-Báez, Almudena; Caldevilla-Domínguez, David (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
If neurocommunication intends to address the way in which the brain reacts to stimuli, digital entertainment is increasingly the means by which these stimuli are administered. In a more varied and intense way. The proliferation of devices that increasingly free video games from their domestic cages is dragging itself into the future with the announcement of the metaverse. With the promise of a revolution in virtual reality long awaited by generations that have lived immersed in the hopeful and exemplary omens of literary and cinematographic science fiction.